1990
DOI: 10.1080/01459740.1990.9966022
|View full text |Cite
|
Sign up to set email alerts
|

The forty‐day rest period and infant feeding practices among Negev Bedouin Arab women in Israel

Abstract: Four hundred and twelve Bedouin Arab women were interviewed within 48 hours of delivering a newborn in 1982 and two months later to examine the effect of social support during the forty-day postpartum rest period on the incidence of exclusive breast feeding at two months. Whereas the distribution of infant feeding practices at two months did not differ among women with and without support during the "forty days," the number of days of help during the "forty days" was significantly associated with type of feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…To our knowledge, this study is the first in the Middle East to examine the prevalence and predictors of EBF during the 40-day rest period. From a nationally a Data are presented as adjusted odds ratio (95% confidence interval) 1 The reference category is Mixed feeding; 2 The reference category is EBOT EBF Exclusive breastfeeding; EBOT Exclusive bottle feeding representative survey in Lebanon, we report a prevalence of EBF of 41.5% at 40 days and 12. 3% at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this study is the first in the Middle East to examine the prevalence and predictors of EBF during the 40-day rest period. From a nationally a Data are presented as adjusted odds ratio (95% confidence interval) 1 The reference category is Mixed feeding; 2 The reference category is EBOT EBF Exclusive breastfeeding; EBOT Exclusive bottle feeding representative survey in Lebanon, we report a prevalence of EBF of 41.5% at 40 days and 12. 3% at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Many societies in the Middle East observe a 40-day postpartum period of rest, seclusion, and ritual that helps establish and maintain breastfeeding [1,2] and protects the mother and newborn from illnesses [3]. During this 40-day rest period, the mother often stays at home and receives help with household chores and congratulatory visits from related women and neighbors [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examined among the Negev Beduin Arab Women in Israel (a society in which the women multitask continuously), it was shown that when ''help'' was available, the odds of maintaining exclusive breast feeding were greater. 29 N Drinking at least 1800 ml fluids-''in order to increase milk production, you must drink more''-is a common piece of advice given to nursing women. In a carefully planned, crossover study of breastfeeding mothers, an increase of at least 25% in fluids intake had no effect on mean daily milk production.…”
Section: How To Increase the Milk Supply?mentioning
confidence: 99%
“…Social environments have also been shown to be important predictors of breast-feeding behavior. Extended kin networks can provide support for breast-feeding mothers by relieving them of their usual household and economic obligations (Forman et al 1990). Gender relations also have an impact, as in Zimbabwe, where a woman cannot terminate breast-feeding without consulting her husband or mother-in-law (Cosminsky et al 1993).…”
Section: Synthesis: Parent-offspring Conflict and The Cultural Ecologmentioning
confidence: 99%